Cell Senescence Methods and Protocols - Galluzzi, Lorenzo; Vitale, Ilio.; Kepp, Oliver; Kroemer, Guido; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Cell senescence is the process whereby cells permanently lose the possibility to proliferate without undergoing cell death, and occurs in a plethora of distinct model organisms. In Cell Senescence: Methods and Protocols, expert researchers in the field detail the methods that are now commonly used to study cell senescence, in model organisms encompassing bacteria, fungi, worms, flies, zebrafish, and mammalian cells. These techniques cover the study of all the morphological, biochemical and functional manifestations of senescence at the cellular level and include protocols for population analyses and high-throughput approaches in suitable model organisms. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.
Keywords: Cell biology; Cell physiology; Cell Biology; Cell Physiology